Kajian Peran Stakeholder terhadap Pembangunan di Kabupaten Pangandaran - Nabila Amalia; Ernady Syaodih; Nia Kurniasari (UNISBA Press, 2023)
Abstract. Sustainable development is a development process that can improve economic levels while maintaining environmental sustainability and social conditions for current and future generations. Problems in regional development can be explained as a gap between the development results that have been achieved at this time and those planned. Pangandaran Regency as one of the New Autonomous Regions is still preparing its government regarding the role of stakeholders and regional development issues such as less than optimal coordination, planning that is less applicable to problems and governance, improving the quality of regional infrastructure, improving the quality of human resources and optimizing PAD management. Therefore, the author identifies the role of stakeholders towards development in Pangandaran Regency. The purpose of this study is to identify the role of stakeholders, strategic goals and improvement efforts that are in accordance with the objectives and priorities of development in Pangandaran Regency. The method used in this research is MACTOR analysis. From the analysis, it was found that the most influential stakeholders in the development of Pangandaran Regency are DPRD, BAPPEDA and DPUTRPRKP Pangandaran Regency. With efforts to increase development efforts based on recommendations based on objectives and priorities in infrastructure services, control of land use change, natural disaster prone management, suppression of growth and occupation rates and coordination between institutions in development in Pangandaran Regency. Abstrak. Pembangunan yang berkelanjutan sebagai suatu proses perkembangan yang dapat meningkatkan tingkat perekonomian menjaga kelestarian lingkungan dan keadaan sosial untuk generasi sekarang dan generasi masa depan. Permasalahan dalam pembangunan daerah dapat dijelaskan sebagai kesenjangan antara hasil pembangunan yang telah dicapai saat ini dengan yang direncanakan. Kabupaten Pangandaran sebagai salah satu Daerah Otonomi Baru yang masih mempersiapkan pemerintahannya terkait peran stakeholder dan permasalahan pembangunan daerah seperti kurang optimalnya koordinasi, perencanaan yang kurang aplikatif dengan permasalahan dan tata kelola pemerintah, peningkatan kualitas infrastruktur wilayah, peningkatan kualitas SDM dan pengoptimalan pengelolaan PAD. Maka dari itu penulis mengidentifikasi peran stakeholder terhadap Pembangunan di Kabupaten Pangandaran. Tujuan dari penelitian ini untuk mengidentifikasi peran stakeholder, tujuan strategis dan upaya peningkatan sesuai dengan tujuan dan skala prioritas Pembangunan di Kabupaten Pangandaran. Metode yang digunakan dalam penelitian ini adalah. analisis MACTOR. Dari hasil analisis didapatkan bahwa stakeholder yang paling berpengaruh dalam Pembangunan di Kabupaten Pangandaran yaitu DPRD, BAPPEDA dan DPUTRPRKP Kabupaten Pangandaran. Dengan upaya peningkatan upaya pembangunan berdasarkan rekomendasi berdasarkan tujuan dan skala prioritas dalam pelayanan infrastruktur, pengendalian alih fungsi lahan, penanggulangan rawan bencana alam, menekan tingkat pertumbuhan dan pendudukan dan koordinasi antar kelembagaan dalam pembangunan di Kabupaten Pangandaran.